Kebijakan Perpajakan, Transfer Pricing dan Nilai Perusahaan - Putu Eka Putri Anagayanti (Universitas Pendidikan Nasional, 2018)
ABSTRACTThe purpose of this research is to test and analyze tax contribution, tunneling incentive and profitability to transfer pricing and firm value. This research uses descriptive research method. The variables tested in this research are company tax efficiency, tunneling incentive, profitability, transfer pricing and firm value. The population taken for this research are non-financial companies that has been listed on the Indonesia Stock Exchange in 2016 with 160 data samples taken using purposive sampling technique. Data analysis in this research was done by path analysis. This study results: (1) taxes contribute to transfer pricing positively and significantly; (2) tunneling incentive contributes to transfer pricing positively and significantly; (3) profitability contributes to transfer pricing positively and significantly; (4) taxes contribute to firm value positively significant; (5) profitability contribute to firm value positively significant; (6) transfer pricing contributes significantly to the value of the firm.